2020
DOI: 10.1620/tjem.252.63
|View full text |Cite
|
Sign up to set email alerts
|

Focal Parenchymal Atrophy and Fat Replacement Are Clues for Early Diagnosis of Pancreatic Cancer with Abnormalities of the Main Pancreatic Duct

Abstract: Pancreatic cancer is one of the most dangerous solid tumors, but its early diagnosis is difficult. The abnormality of the main pancreatic duct (MPD), such as a single localized stricture and upstream dilatation, might be useful in the early detection of pancreatic cancer. However, these findings are often observed in benign inflammatory cases. This study aimed to clarify whether early pancreatic cancer presenting MPD abnormalities has characteristic features different from those of benign cases. This is a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In this case–control study, we showed that FPA, which has been reported as a characteristic imaging sign of early stage PDAC [ 13 , 14 , 15 ], was observed in about one-third of the patients at least 6 months before PDAC diagnosis ( Figure 3 ). FPA was more frequently observed in patients with PDAC than sex- and age-matched controls without PDAC.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…In this case–control study, we showed that FPA, which has been reported as a characteristic imaging sign of early stage PDAC [ 13 , 14 , 15 ], was observed in about one-third of the patients at least 6 months before PDAC diagnosis ( Figure 3 ). FPA was more frequently observed in patients with PDAC than sex- and age-matched controls without PDAC.…”
Section: Discussionmentioning
confidence: 57%
“…PDAC in the uncinate process, especially at PDAC at an early stage, can be overlooked on imaging owing to the absence of biliary or pancreatic ductal dilatation [ 11 ]. MPD dilation, which is another important clue for the early diagnosis of PDAC [ 11 , 12 , 13 ], is recognized more easily in the pancreatic body and tail than in the pancreatic head because MPD is intact in the pancreatic head [ 13 ]. Notably, Matsudo et al [ 25 ] reported that carcinoma in situ was observed more frequently in the pancreatic body and tail than in the pancreatic head in autopsied cases, suggesting that the mechanism of carcinogenesis differs depending on the tumor location in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations